Depth profiling and morphological characterization of AlN thin films deposited on Si substrates using a reactive sputter magnetron. Issue 2 (1st August 2014) - Macchi, Carlos; Bürgi, Juan; García Molleja, Javier; Mariazzi, Sebastiano; Piccoli, Mattia; Bemporad, Edoardo; Feugeas, Jorge; Brusa, Roberto Sennen; Somoza, Alberto
Abstract : It is well-known that the characteristics of aluminum nitride thin films mainly depend on their morphologies, the quality of the film-substrate interfaces and the open volume defects. A study of the depth profiling and morphological characterization of AlN thin films deposited on two types of Si substrates is presented. Thin films of thicknesses between 200 and 400 nm were deposited during two deposition times using a reactive sputter magnetron. These films were characterized by means of X-ray diffraction and imaging techniques (SEM and TEM). To analyze the composition of the films, energy dispersive X-ray spectroscopy was applied. Positron annihilation spectroscopy, specifically Doppler broadening spectroscopy, was used to gather information on the depth profiling of open volume defects inside the films and the AlN films-Si substrate interfaces. The results are interpreted in terms of the structural changes induced in the films as a consequence of changes in the deposition time (i.e., thicknesses) and of the orientation of the substrates.